Determinants of sustainable development in Africa : an empirical analysis from CEMAC countries - Yute, Idris Taliedje (My University, 2022)
Our research objective is based on the contribution of factors like population, finance, demography, foreign investment, technology, health, domestic investment, environment, and governance to economic growth in the CEMAC zone over the period 2000-2018, more precisely, our thesis objective is to identify factors which impact the development of countries of the CEMAC zone and not just taking into consideration control variables but adding to its foreign direct investment. This analysis is being done using data of the World development indicators 2018. On the one hand, we first showed a detailed comprehensive portrait of the relations that exist between foreign investment and economic growth, theoretically and later on present the united nation recommendation concerning the development of the 21st century, which is the sustainability of the economies in the CEMAC zone. We made use of the multiple linear regression model to explain our selected variables; and more still, we examine the effects of our control variables on economic growth to observe the potential limits of sustainable development in the CEMAC zone by estimating our model. Therefore, it appears that foreign direct investment does not contribute to the creation of economic growth within the CEMAC zone over the selected study period and that in the CEMAC zone, domestic investment favors foreign investment which is being proven by the fact that finance (domestic investment and foreign investment) influences economic growth in the CEMAC zone. It is therefore up to the States of the CEMAC zone to develop incentives to invest in every sector of activities since they are only investing in processing chains of extractive companies which do not affect the real standard of the economy and do not affect the standard of living.

Araştırma hedefimiz 2000-2018 döneminde nüfus, finans, demografi, yabancı yatırım, teknoloji, sağlık, yerli yatırım, çevre ve yönetim gibi faktörlerin ekonomik büyümeye katkısı tez hedefimize dayanmaktadır. CEMAC bölgesindeki ülkelerin gelişimini etkileyen faktörleri belirlemek ve sadece kontrol değişkenlerini hesaba katmakla kalmayıp aynı zamanda doğrudan yabancı yatırıma da denkleme dahil ettik. Bu analiz, 2018 Dünya kalkınma göstergeleri verileri kullanılarak yapılmıştır. Bir yandan, önce teoride yabancı yatırım ile ekonomik büyüme arasında var olan ilişkilerin ayrıntılı ve kapsamlı bir portresini, ardından da 21. yüzyıl CEMAC bölgesindeki ekonomilerin sürdürülebilirliğini gösterdik. Seçilmiş değişkenlerimizi açıklamak için çoklu doğrusal regresyon modelini kullandık; ve modelimizi temel alarak CEMAC bölgesindeki sürdürülebilir kalkınmanın potansiyel sınırlarını gözlemlemek için kontrol değişkenlerimizin ekonomik büyüme üzerindeki etkilerini inceledik. Yabancı yatırımlar doğrudan, seçilen çalışma döneminde CEMAC bölgesindeki ekonomik büyümenin yaratılmasına katkıda bulunmaz ve CEMAC bölgesindeki yerel yatırım, CEMAC bölgesindeki ekonomik büyümeyi etkileyen yabancı yatırımı destekler. Bu nedenle, yalnızca ekonominin gerçek standardını etkilemeyen ve yaşam standardını etkilemeyen madencilik şirketlerinin işleme zincirlerine yatırım yaptıklarından, faaliyetlerin her sektörüne yatırım yapmak için teşvikler geliştirmek CEMAC bölgesinin Devletlerine kalmıştır.
Afrika'da sürdürülebilir kalkınmanın belirleyicileri : CEMAC ülkelerinden ampirik bir analiz
Keywords: CEMAC; Development; Doğrudan Yabancı Yatırım; Domestic investment; Economic; Ekonomik Büyüme; Finance; Foreign direct investment; growth; Implementation; Kalkınma; Maliye; Sustainability; Sürdürülebilirlik; Uygulama; Yerli Yatırım